The Basics About Community Based Research - Leite, Sónia Ruão (Advances in Social Sciences Research Journal, 2019)
As Community Based Research (CBR) gains currency as a ‘research strategy of choice’ for the community sector (and increasingly establishes itself as a credible research approach also in the academic sector) we believe there is a need to revisit what have become the conventions of CBR and consider how these are enacted in practice. If local research that is community based, community driven or community-centered is to assume a position of credibility in the social and health sciences, for more focus on quality of life, and create meaningful social and political change at local, regional and systemic levels, including the social, economic, and political dimensions of health and well-being we need to consider the current state of CBR and identify steps forward for its use. Thus, this paper aims to understand the current state-of-the art concerning CBR.